Low Thresholds and Tunable Modes in Plasmon‐Assisted Perovskite Microlasers. Issue 12 (8th April 2022) - Li, Ziwei; Wang, Yajuan; Li, Lihui; Xie, Yunfei; He, Chenglin; Xu, Pan; Zhang, Xuehong; Huang, Jianhua; Huang, Ming; Yang, Liuli; Du, Juan; Zhu, Xiaoli; et al.
Abstract: Low‐dimensional perovskite structures are ideal materials for nano/microlasers owing to their excellent optical gain properties and high emission efficiency. But it is still a challenge to achieve single‐mode and tunable lasing behaviors in micro‐scale perovskite, especially showing ultralow thresholds in tens of µJ cm −2 . In this work, CsPbBr3 /Ag hemispheroids have been synthesized in a designed chemical vapor deposition (CVD) process. Benefiting from the whispering gallery resonance mode and plasmon‐enhanced light–matter interactions in well‐confined hybrid cavities, the CsPbBr3 /Ag plasmonic microlasers exhibit low pump thresholds down to 35–51 µJ cm −2 . Interestingly, single‐mode and two‐mode lasing behaviors are determined by the morphology of plasmonic Ag nanostructures, and lasing modes could be selectively tuned by increasing the pump fluence accompanying with dynamic competitions of photonic and plasmonic modes. Simulations of electromagnetic field have been plotted to show near‐field resonant modes for a comprehensive understanding of plasmon‐assisted lasing. These results not only provide a solution to fabricate low‐threshold plasmonic microlasers, but also advocate the prospect of all‐inorganic perovskite nanostructures as promising candidates for on‐chip integrated light sources. Abstract : CsPbBr3 /Ag hemispheroids are designed and synthesized exhibiting low thresholds and tunable modes lasing, which are benefited from the whispering gallery resonance mode and plasmon‐enhanced light–matter interactions. Single‐mode and two‐mode lasing behaviors are detected in heterostructures with different plasmonic Ag nanostructures, which could be confirmed by electromagnetic field simulations.